Prototype Smart Car Mecanum Wheel Fire Extinguisher Based On Esp 32 Cam With Bluetooth Combination - Bambang Dwinanto; Abdurrazaq Afiif Lubis; Mochammad Karjadi; Bambang Yulianto; Bambang Harianto (Publikasi Indonesia, 2023)
The development of microcontroller technology has been implemented in the robotics industry, particularly in performing tasks that are risky for living beings, especially humans. In this context, a wheeled smart car robot can automatically extinguish fires. The fire extinguishing system is taken over by the robot's system when fire or heat is detected, and the robot's controller activates the extinguishing system, spraying water at the fire point. The ESP 32 CAM microcontroller serves as the processing and controlling unit, handling data and displaying real-time camera images to ensure accurate fire extinguishing. Additionally, a mecanum wheel drive mechanism is added to enhance the robot's movement flexibility.